ΘΕΜΑΤΑ ΕΜΕ Γ ΛΥΚΕΙΟΥ 2014

  • View
    548

  • Download
    0

Embed Size (px)

DESCRIPTION

2014

Transcript

  • skas

    iarxeio

    pro.blogspot.gr

  • 1

    = +

    -

    - -

    + + + ... +=

    + + + ... +

    - + + =

    = = -1

    + ++ = -

    + = -

    :

    i 5 = i 41+1 = i , i 9 = i42+1 = i ,.., i 4-3 = i 4( -1)+1 = i

    z 2 = (x + xi)2 = x2 + 2x2i - x2 = 2x2i

    :

    z 4 + z 8 + z12 + ... + z 4

    i z 2 + i 5z 6 + i 9z10 + ... + i 4-3z 4-2 =

    z2 (z2 + z6 + z10 + ... + z4-2 )=

    i (z2 + z 6 + z 10 + ... + z4-2 ) =

    z 2 2x2i 2= = = 2x2 = Im(z )i i

  • 2

    :z3 = z z2 = (x + xi) 2x2i = -2x3 + 2x3i

    :

    z 3 - z2 + z + i = 0 (-2x 3 + 2x 3i) - 2x 2i + (x - xi) + i = 0

    - 2x3 + x = 0( x3 x ) ( x3 x2 x 1) i 0

    x3 x2 x 1 0 -2 + + 2 - 2 - + =

    2 - 2 - + =

    2x3-x = 0 2x3-x = 0 x (2x2 -1) = 0

    ( x3 x) x2 1 0 x2 1 0 x2 1 0

    2

    -

    - 2

    +

    =

    - 2

    +

    =

    2 - =

    2x2 -1= 0 2x2 =1 x2 = 1

    x = 2

    2 2:

    z1 = 2

    (1+ i)2

    z2 = - 2

    (1+ i)2

    :

    4 2z1 (z1) (1 i) (1 i 1) 4i 12

    = 2 = 1 + 2 =

    1 + 2 - 2 = 1 2 = - 2 4 4

    (1)

    z2 = - 2

    (1+ i) = -z12(2)

    :

    4 4 42 1 1

    (1)

    z = (-z) = z = -1

    :2 2 3 2 3 2

    1 1 2 2 1 1 2 2

    2 1 1 2

    (2)z + z+

    z + z=

    z + z + z + z=

    z z zz

    3 2 3 2

    = z1 +z1 + (-z1) + (-z1) =

    z1(- z1)3 2 3 2 2z1 z1 z1 z1 2z1

    2 21 1

    2z z

    + - += = = -

    - -

    :

    z12014 z1

    4503+2 (z14 )503

    z12

    (1)

    ( 1)503 z12 z1

    2= = = - = - =

    2

    (1 i) (1 i 1) i i 2 1 1

    = - + = - + 2 - = - 2 = - 2 2 2 (3)

    2014 (2)

    2014 2014 (3)

    z2 = (-z1) =z1 = - i

    :2014 2014z1 + z2 = (-i)+ (-i) = -2i

  • 3

    - + =

    = + =

    =

    4w 2 -2w +1 = 0 D = (-2)2 - 4 4 1 = -12 < 0

    : w = 1

    i3

    4 4

    z1

    2

    = wz

    . z1 = 1 z1 0 , w 0 , (2)

    :

    4w + 1

    =2 4w 2 -2w + 1 =0 w =

    1

    i

    3

    z1 = 1

    i

    3

    w 4 4 z 2 4 4

    z1 =

    1 i

    3=

    1,

    z2 4 4 2

    (1 1)z1

    2

    z 2 2z 2= =

    , 0 , z1 z 2 , :

    2 2 2(O) = z1 = 1 = 1, (OB)2 = z2

    2 = 22 = 4

    :2 2 2 2 2 24z1 + z2 = 2z1z2 (z1- z2 ) = -3z1 |z1- z2| = 3 |z1| |z1- z2|= 3

    :2() = 3 () = 3

    :

    (OB)2 =(O)2 +(B)2 ,

    .

    O=900

    (OA) = (OB)

    2,

    OBA 300

    = AOB 600

    =

  • 4

    + + - = +

    - =

    - = + -

    :

    2 2 ( )( )w1 w2 w1 w2 w1 w2 w1 w2 ( w1 w2 ) (w1 w2 )+ + - = + + + - - =

    = ( w1 + w2 )( w1 + w2 ) + ( w1 - w2 )( w1 - w2 ) =

    = w1w1 + w1w2 + w1w2 + w2w2 + w1w1 - w1w2 - w1w 2 + w 2w 2 =

    2 2= 2w1w1 + 2w2w2 = 2w1 + 2w2

    z = x + yi, x ,yR M(x, y)

    z -2i =1 z-( 0 +2i ) =1 ()=1, (z) z (0 ,2)z (0,2)

    1

    z

    (0,2) =1, z -2i =1

    z1, z 2 z -2i =1,:

    z1 - 2i =1 z2 - 2i =1

    w1 = z1 - 2i w 2 =z2 - 2i ()

    :

    (z1 - 2i) + ( z2 - 2i)2 + (z1 - 2i) - ( z2 - 2i)

    2 = 2 z1 - 2i

    2 + 2 z2 - 2i2

    2 2 2 2z1 + z2 - 4i + z1 - z2 =2 1 + 2 1

    2z1 + z2 - 4i +1= 4

    z1 + z2 - 4i = 3

  • 5

    ( - ) = ( - )

    = +

    =

    = -

    -

    (1):

    (3z -2i)2013 = (iz -6)2013 (3z-2i) 2013= ( iz -6) 2013

    ( 3z - 2i) = (i z - 6) ( 3z - 2i) 2 = (i z - 6) 2

    ( )( ) ( )( ) 3 z - 2 i 3 z + 2 i = iz -6 - iz -6

    9 z 2 + 6iz - 6i z + 4 = z 2 + 6iz - 6i z + 36

    8 z 2 = 32 z 2 = 4 z = 2

    :

    z = 2 z 2 = 4 z z = 4 4

    = z (3)z

    z = x + yi x ,yR ,:

    42014 (3)

    u = z - = (z- z)2014 =(2 yi)2014 = z

    = (2 y)2014 i2014 = (2 y)2014 i2 = - (2 y)2014 R

    u R

    :

    2014 2014 ( )2014 4028(3)2014

    u = z - 4 = (z- z) = z- z z + z = 2 z

    :

    u 24028

  • 6

    w1 = 1+ 2 z1 i w 2 = 1+ 2 z2 i, z1, z 2

    (1), z1 = z2 = 2 . z1 , z2 O(0, 0) r = 2 , z1 -z2 4

    :

    w1 - w 2 = 1+ 2z1i -1- 2z2i = 2i (z1 - z2 ) =

    = 2 i z1 - z2 = 2 z1 - z2 = 2 z1 - z2 2 4 = 8

    - + = + + + =

    + + +

    - + +

    + +

    :

    |z 2 - 2zi| +2|z| = 2+ |z + 2i|

    |z| |z - 2i| + 2|z| = 2+ |z - 2i|

    | z | | z - 2i | - | z - 2i | +2 | z | -2 = 0

    ( ) (|z - 2i| |z| -1 + 2 |z| -1) = 0

    (| z | -1)(| z - 2i | +2 ) = 0 |z| = 1 (1), | z - 2i | +2 0 z C: x2 + y2 =1 (0,0) r =1

    w :

    |w +3z | + | 2w +5z |= |w +3z | +2w + 5 z2

    |w +3z |+ w + 5 z (w +3z) - (w + 5 z) = 1 | z |= 1 1= 12 2 2 2 2

    1|w + 3z| + |2w + 5z|

    2

  • 7

    :(1)

    22| z -1 + z +1| | z +1 + z | +1 = 4.:

    | z -1 + z2 +1| | z -1+ z2 +1| = | z(z +1) | = | z | | z +1 | (2)

    | z |=1 (2) | z -1 + z2+1| | z +1| (3)

    | z -1 + z2+1| | z -1| (4)

    z = x + yi x,y[ -1,1] : | z | =1| z |2 =1 x 2 + y 2 =1 (5)

    (5)

    2 2 2 2| z +1| = (x +1) + y = x + y + 2x +1 = 1+ 2x +1= 2(1+x) = 2 1+x (6)

    (5)

    2 2 2 2| z -1| = (x -1) + y = x + y - 2x +1 = 1- 2x +1= 2(1-x) = 2 1-x (7)

    (3) (6) :

    | z -1 + z2+1| 2 1+x (8)

    (4) (7) :

    | z -1 + z2+1| 2 1-x (9)

    x[ 0 ,1] (8):| z -1 + z2+1| 2

    x[ -1, 0] (9):| z -1 + z2+1| 2

    :2 |z - 1 | + |z 2 + 1 | 4

    zC | z | =1 :

    |z 2 + uz + v|< 1 (10)

    (10) z =1 z = -1:|1+ u + v | | 2+2v|2>2|1+ v|| v+1|2|-1+ v|| v-1|| v+1|+ | v-1| | (v+1)- (v-1)| 2 >2

    .

    zo C |zo | =1,2|zo + uzo + v|1

  • 8

    -

    - - =

    - + = + -

    - - + +

    = ( - ) - - - - -

    :

    112

    3

    2

    13i

    22

    1

    2

    3i1

    2

    3i1 25

    2522252525

    ==

    -+

    =-=

    -=

    -

    ( )25

    z 3 3i 2 1 i 3

    z 3 3i 22

    - - - = - + =

    z ( 3 , 3) = 2 z z) x Re( - k , x = 3

    ( , ) = 2:

    Re(z)- x x - Re(z) x +

    3- 2 Re(z) 3+ 2 1 Re(z) 5

    Re(z) 1 z =1 + 3i , 5 z = 5 + 3i

    :

    z (3 + 3i) = 2z=x+yi

    - (x - 3)2 + (y - 3)2 = 4

    (x - 3)2 4 x -3 2 -2 x - 3 2 1 x 5

    Re(z) 1 z =1+3i , 5 z =5 +3i

  • 9

    :

    2 w -3+3i = iz +3-3i 2 (w -3-3i) = i(z -3-3i) )

    2w -3-3i = i z -3-3i 2w -3-3i =2 w -3-3i =1 w - (3+3i) =1 w ( 3 , 3) r1 =1

    z w () ():

    z - w = ( z - (3+3i)) - ( w - (3+3i)) = u - v

    z (3 3i)u = - + v = w - (3+ 3i) u =2 v =1:

    2 1 3vuvuwz - = - + = + =

    2 1 1vuvuwz - = - - = - =

    3w1 z -

    .

    :z + w = (z - (3+ 3i)) + ( w - (3+ 3i)) + 6(1 + i) = u + v +6(1+ i)

    :

    3262612i)6(1vui)6(1vuwz + = + + + + + + = + + = +

    ( ) ( )z + w = u + v +6(1 + i) 6(1 + i) -u + v 6(1 + i) - u +v = 6 2 -3 = 6 2 -3

    6 2 3wz36 2 - + +

  • 10

    :

    ) ( ) 6 2 3(MNw)(zwz + = - - = B = +

    ) 6 2 3()(MNw)(zwz + = - - = AG = - ,

    u = z - (3+ 3i), :23i)(3u = z - + = (1)

    u = 2 u 2 = 4 u u = 4 u = 4 (2)

    u z1 , z2 z,:

    ( 1 2 )1 2

    1 1 k = z - z - =

    z - 3 - 3i z - 3 - 3i

    (( 1 ) ( 2 ))1 2

    1 1 = z -3-3i - z -3-3i - = z -3-3i z -3-3i

    ( ) ( )( 2 )

    1 2 1 21 2 1 2

    1 1 1 4 4 = u - u - = u - u - = u u 4 u u

    = 1 ( u1 -u2 )( u1 - u2 ) =

    1 ( u1 - u2 )( u1 - u2 ) = 1 u1 - u2 24 4 4 k :

    k = 1u1 - u2

    2 0 4

    k1

    u1 u22 1 ( u1 u2 )

    2 (1)1(2 2)2 4

    4 4 4= - + = + =

    0 k 4

    + = +

    =

    + > <

    - + + + =

  • 11

    :

    iz +8 = 2 2iz +1 iz +8 2 = 4 2iz +1 2

    (iz + 8)(iz + 8) = 4 (2 iz + 1)(2 iz + 1)

    (iz + 8)(-iz + 8) = 4(2iz +1)(-2iz +1)

    z2 + 8iz- 8iz + 64 =16 z 2 + 8iz- 8iz + 4

    15z2 = 60 z 2 = 4 z = 2

    z (0,0) = 2

    :z1 = 2 z2 = 2

    :

    1 2 1 2 1 2 1 2z + x z > 3 z + x z2 > 3 (z + x z ) (z + x z ) > 3

    1 2 1 2 1 1 2 1 2 2(z + x z ) ( z + xz ) > 3 z2 + x z z + x z z + x 2 z

    2 > 3

    1 2 1 2 1 2 1 24x2 + (z z + z z ) x +1 > 0 4x2 + (z z + z z ) x +1 > 0

    1 24x2 + 2Re(zz ) x +1 > 0 , xR

    4x2 + 2Re(z1z2 ) x +1 :

    0 ( 2 -1)( z 2 -4) > 0 (3)

    ( -1,1) 2 -1< 0 (3) :

    z 2 - 4 < 0 z 2< 4 z < 2 ,, z > 2

  • 12

    z 2 ,.

    z = 2 , z,

    (1)C : x 2 + y 2 = 4 , () .

    z = 0 , (1) 16 = 0 ,. z 0 :

    z2 0

    z4 2z3 8z 16 0

    z2 28 16 2 16 4zz z2

    0 zz2

    zz

    0 (4)+ + + = + + + = + + 2a + =

    z + 4

    = u (5), :z

    4 2 2 4 16 2 2 16 2z u z z 2 u z 2 u 8 ,z z z z +

    2

    = + 2 + = + = -

    (4) :

    (u2- 8) + 2au =0 u2+ 2au -8 =0 (6):

    D = 42 +32 = 4(2 +8) >0 (6) :

    2 8 2u = -

    2a

    2

    +

    = - a +82

    (7)

    (5) :

    ( )(7)z2 - uz + 4 = 0 z2 + a 2 +8 z + 4 = 0 (8):

    ( ) ( )2D = a 2 +8 -16 = 2 +2 +8 2a 2 +8 -16 = 2 2 -4 a 2 +8 -1

  • 13

    y = 0 , z = x + 0 i = xR () z =2z= 2

    z = 2 :

    24 + 2 23 + 8 2 + 16 = 0 = -1,, (-1,1)

    z = - 2 :

    (-2)4 + 2 (-2)3 + 8 (-2) + 16 = 0 =1,, (-1,1)

    y 0

    x = 0 , z = 0+ yi = yi I () z =2z= 2i

    z = 2i :

    (2i)4 + 2 (2i)3 + 8 2i + 16 = 0

    24 i4 + 2 23i3 +8 2i + 16 = 0

    16-16i + 16i + 16 = 0 32 = 0 ,.

    z = - 2i :

    (-2i)4 + 2 (-2i)3 + 8 (-2i) + 16 = 0

    24 i4 + 2 (-2)3 i3 -8 2i + 16 = 0

    16 +16i -16i +16 = 0 32 = 0 ,. x 0 (1) x + yi xy 0

    [ ]= =

    - =

    =

    = -

    - [ ]

    z = x + yi, x , yR M(x , y).

    :